Pronunciation Errors of the Hijaiyah in Students of Nurussalam Grade VII of Junior High School Barito Kuala South Kalimantan - Fahrurrazi, A. (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
The aim of this research is to identify forms of errors in the pronunciation of hijaiyah letters among class VII students at MTs Nurussalam when reading Arabic texts and the factors behind them. The approach in this research is descriptive qualitative with a field study type. The data in this research are the results of audiovisual recordings of students reading Arabic texts in the first lesson about ta'aruf. The data source in this research was class VII MTs students with a total of 25 students, and were selected using simple random sampling. The data collection technique uses listening, interviews and observation techniques, while the data analysis technique uses six stages. The results of the research show that it is known that the number of errors in the pronunciation of hijaiyah letters in reading Arabic texts reaches 60% in the form of errors in changing the pronunciation of consonant letters to other letters such as changing the letter ذ to ز, changing the letter ع to أ, the letter ش, ص to the letter س , the letter ط becomes ت, the letter ح becomes ه, the letter ز becomes ج, the letter ق becomes ك, while the factors that cause these errors include: Habitual factors from the environment, the influence of the first language in the form of Banjar dialect, and difficulty identifying the location of articulation.